Costs in the Norwegian Payment System 2007 - a Brief Overview of the Surveys and Results - Olaf Gresvik; Harald Haare (Norges Bank, 2008)
The analysis covers social costs associated with payment cards, giros and cash. The bulk of retail payments in Norway are settled by means of these instruments. The social costs of using and producing these payment services are estimated to be NOK 10.97 billion in 2007, equivalent to 0.48 % of GDP1. The costs estimated cover activities by banks, subcontractors, the central bank, households and merchants (point of sale). Our household survey indicates that cash payments account for as little as 14 % of the value of payments and 24 % of the number of transactions at point of sale in Norway. However, as demonstrated in Gresvik and Haare (2008), other sources of information and other methods give other estimates. The value of cash payments at point of sale could be as high as 38 % of the total value. Our results indicate that the efficiency of the Norwegian payment system has improved since 2001. We find that unit cost incurred by banks for the most popular payment instruments have decreased, and that the cost recovery for payments in the banking industry has increased since 2001.
hdl:11250/2507959
Keywords: 330